INTERPROFESSIONAL COMMUNICATION AND JOB SATISFACTION AMONG NUTRITION AND EPIDEMIOLOGY TECHNICIANS IN SAUDI ARABIA: A CROSS-SECTIONAL STUDY - Mohammad Musajal Hailan Alanazi, Maha Gadhban Bashr Al Enazi, Ghazi Turki Lofan Aldhafeeri, Rasheed Rahi Giza Alanazi; Seadi Brekah Mudaf Almutiri, Nader Jerry Sady Almotry, Ali Abdullah M Alnattar (Chelonian Research Foundation, 2022)
Background: Interprofessional communication is a critical component of effective healthcare delivery and has been linked to job satisfaction among healthcare professionals. However, little is known about the relationship between interprofessional communication and job satisfaction among nutrition and epidemiology technicians in Saudi Arabia. This study aimed to examine the perceptions of interprofessional communication and job satisfaction among these healthcare professionals, and to identify the predictors of job satisfaction. Methods: A cross-sectional study was conducted among 432 nutrition and epidemiology technicians working in various healthcare settings in three regions of Saudi Arabia (Riyadh, Jeddah, and Dammam) between January and March 2023. Participants completed a self-administered questionnaire that included demographic and work experience variables, the Interprofessional Communication Scale (ICS), and the Job Satisfaction Survey (JSS). Descriptive statistics, independent samples t-tests, one-way analysis of variance (ANOVA), and multiple regression analysis were used to analyze the data. Results: The majority of participants were female (63%), Saudi nationals (92.1%), and had a diploma degree (79.6%). The overall scores on the ICS (M = 3.65, SD = 0.62) and JSS (M = 4.11, SD = 0.72) indicated moderate to high levels of interprofessional communication and job satisfaction, respectively. Pharmacy technicians had significantly higher scores on the ICS than nutrition and nursing technicians, while healthy assistants had significantly higher scores on the JSS than nutrition and nursing technicians. Multiple regression analysis identified communication openness (β = 0.28, p < 0.001), communication with physicians (β = 0.15, p = 0.004), communication with other healthcare professionals (β = 0.13, p = 0.011), and healthcare role (β = -0.11, p = 0.007) as significant predictors of job satisfaction, controlling for demographic and work experience variables. Conclusion: Interprofessional communication is an important predictor of job satisfaction among nutrition and epidemiology technicians in Saudi Arabia. Healthcare organizations should prioritize the development and implementation of interventions to enhance interprofessional communication and collaboration, such as training programs, team-building activities, and recognition and rewards systems, to improve the well-being and performance of these healthcare professionals and the quality of patient care. Keywords: Interprofessional communication, job satisfaction, nutrition technicians, epidemiology technicians, Saudi Arabia